Comprehensive relationships between kinetic energy and rainfall intensity based on precipitation measurements from an OTT Parsivel2 optical disdrometer - Van, Linh Nguyen; Le, Xuan-Hien; Nguyen, Giang V.; Yeon, Minho; May, Do Thi Tuyet; Lee, Giha (Frontiers in Environmental Science, 2022)
When raindrops collide with the topsoil surface, they cause soil detachment, which can be estimated by measuring the kinetic energy (KE) of the raindrops. Considering their direct measurements on terrestrial surfaces are challenging, empirical equations are commonly utilized for estimating the KE from rainfall intensity (Ir), which has a great influence on soil loss and can be easily obtained. However, establishing the optimal relationship between KE and Ir is difficult. In this study, we used a laser-based instrument (OTT Parsivel2 Optical disdrometer) to collect datasets in Sangju City (Korea) between June 2020 and December 2021 to examine the characteristics of KE–Ir relationships. We derived two different expressions for KE–Ir: KE expenditure (KEexp; J m-2h-1) and KE content (KEcon; J m-2mm-1), using 37 rainfall events. We employed statistical analysis to demonstrate that KEexp is more suitable than KEcon for establishing an empirical rule from Ir. We used a power-law model to evaluate the best correlation between KEexp and Ir and an exponential equation to find the best match between KEcon and Ir. Subsequently, the 37 rainfall events were categorized into three groups based on the magnitude of the mean rainfall intensity of each event. Overall, the KE values estimated through the equations derived based on 37 events tended to be overestimated than those estimated by the equations derived based on the three rainfall event groups. Our findings should facilitate the development of more suitable physics-based soil erosion models at event scales.